Pemanfaatan Media YouTube pada Pembelajaran Menulis Naskah Drama Kelas VIII SMP Negeri 4 Singaraja - Triana, Devi; Tantri, Ade Asih Susiari; Nurjaya , I Gede (Jurnal Penelitian Mahasiswa Indonesia, 2023)
This research aims to describe (1) the use of YouTube media in learning to write drama scripts for students at SMP Negeri 4 Singaraja (2) the obstacles in learning to write drama scripts using YouTube media for class VIII students at SMP Negeri 4 Singaraja (3) the results of learning to write drama script using YouTube media for class VIII students of SMP Negeri 4 Singaraja. This study used a qualitative descriptive research design. The subject of this study was a class VIII Indonesian. The data collection methods used are observation, interviews, and documentation. The results of this research show that (1) The implementation of learning to write drama scripts using YouTube media, there are three activities carried out, namely the opening, core, and closing activities in the implementation of learning to write drama scripts. In the opening activity, the writer delivers an overview and learning objectives, in the core activity the teacher shows a video, and students listen to the video being shown, and in the closing activity, the teacher draws conclusions from the lesson. (2) The obstacles in learning to write drama scripts using YouTube media, namely showing, namely, lack of students' focus on learning to write drama scripts due to the different students' abilities -Different in writing drama scripts, time management is still less effective. (3) average score of 85 in the good category. This gives an idea of the extent of students' abilities in writing drama scripts using YouTube media, namely seen from the students' work which is checked by the teacher, and sorted according to the students' abilities from the highest score obtained to the smallest score. The suggestion for this research is that Indonesian language teachers maintain the effectiveness of using YouTube media in learning.